2021
DOI: 10.1101/2021.11.11.467452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine depletion can be predicted by the aperiodic component of subthalamic local field potentials

Abstract: Electrophysiological biomarkers reflecting the pathological activities in the basal ganglia are essential to gain an etiological understanding of Parkinson’s disease (PD) and develop a method of diagnosing and treating the disease. Previous studies that explored electrophysiological biomarkers in PD have focused mainly on oscillatory or periodic activities such as beta and gamma oscillations. Emerging evidence has suggested that the nonoscillatory, aperiodic component reflects the firing rate and synaptic curr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This has led to a hypothesized slowing of brain activity in patients with PD, but it remains unclear whether such a neurophysiological effect relates to clinical features of the disease, and whether any such relationships are of a deleterious or compensatory nature. These multi-spectral deviations from healthy levels also comprise rhythmic and/or arrhythmic components 43-46 , for which clinical interpretation and significance for frequency-specific neuromodulation therapies remain to be established in PD 19,42,47-51 .…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a hypothesized slowing of brain activity in patients with PD, but it remains unclear whether such a neurophysiological effect relates to clinical features of the disease, and whether any such relationships are of a deleterious or compensatory nature. These multi-spectral deviations from healthy levels also comprise rhythmic and/or arrhythmic components 43-46 , for which clinical interpretation and significance for frequency-specific neuromodulation therapies remain to be established in PD 19,42,47-51 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown alterations of arhythmic brain activity in PD patients 12,67,68 . Here we show that the arhythmic component of the neurophysiological spectrum can differentiate between individuals and contributes to the association between inter-individual differentiability and motor symptoms.…”
Section: Discussionmentioning
confidence: 99%